Anti-democratic and racist legacy of policing misdemeanors: A critical literature review of the broken windows theory - Litmanen, Heini (Historiallinen yhdistys, 2025)
James Q. Wilson and George L. Kelling’s broken windows theory has been claimed to change policing in the United States by shifting focus from serious crimes to misdemeanors. Others view the theory as a form of reinstalling vagrancy laws that criminalized African Americans after the abolition of slavery. Through a critical literature review, this article discusses the theory’s theoretical and historical precursors. The theory’s wish to return to an earlier period of policing through wide police discretion and lack of procedural oversight over police work advances anti-democratic and racist goals calling for reduced civil rights for the “undesirables.” By relying on colorblind racism in their history-telling, the theory portrays itself as race-neutral while contributing to racist policing. This article will also contribute to a less discussed aspect of the theory’s approval of community and vigilante policing. Approval of policing by groups historically responsible for racial violence and terror further speaks to the colorblind racism of the theory, leading to dangerous implications for communities of color. Finally, the article will discuss the misdemeanor system as a continuation of vagrancy laws and tie the broken windows theory to punitiveness and anti-democratic ideas firmly rooted in the history of the United States.
James Q. Wilsonin ja George L. Kellingin rikkoutuneiden ikkunoiden teorian on väitetty muuttavan poliisitoiminnan painopistettä Yhdysvalloissa vakavasta rikollisuudesta pikkurikkeisiin. Toiset näkevät teorian pyrkineen irtolaisuuslakien palauttamiseen, jotka olivat keskeisiä afroamerikkalaisten kriminalisoimisessa orjuuden lakkauttamisen jälkeen. Tämä artikkeli tarkastelee teorian teoreettisia ja historiallisia edeltäjiä kriittisen kirjallisuuskatsauksen avulla. Teorian haikailu poliisitoiminnan aikaisempaan aikakauteen poliisin laajan harkintavallan ja poliisityön proseduraalisen valvonnan puutteen kautta edistää demokratianvastaisia ja rasistisia tavoitteita, joilla vaaditaan "ei-toivottujen henkilöiden" oikeuksien heikentämistä. Historiankertomuksessaan värisokeaan rasismiin nojaten teoria esittäytyy rotuneutraalina edistäen samalla rasistista poliisitoimintaa. Tämä artikkeli keskittyy myös vähemmän huomiota herättäneeseen yhteisöiden ja omankädenoikeuden harjoittajien poliisitoiminnan hyväksyntään teoriassa. Rasistiseen väkivaltaan ja terroriin kytkeytyvien ryhmien poliisitoiminnan hyväksyntä kertoo jälleen teorian värisokeasta rasismista, jolla on vaarallisia seurauksia rodullistetuille vähemmistöille. Lopuksi artikkeli käsittelee rikkomusjärjestelmää irtolaislakien jatkona ja sitoo rikkoutuneiden ikkunoiden teorian Yhdysvaltojen historiaan vahvasti juurtuneeseen rankaisukeskeisyyteen ja demokratianvastaisuuteen.